1994
DOI: 10.1090/s0025-5718-1994-1203737-5
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering singularities by discrete methods

Abstract: Abstract. We consider the problem of estimating numerically the parameters of singularities of solutions of differential equations. We propose a novel approach which is based on discretizing the governing equation and "timestepping" in the complex domain. Some applications to ordinary and partial differential equations are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…One example is the study reported in [14], in which Padé approximation was used to study singularity formation in a fluid flow problem. Another study of this type is [17], which includes a test problem similar to (1.2).…”
Section: Introduction Many Nonlinear Pdes Have Solutions That Becomementioning
confidence: 99%
“…One example is the study reported in [14], in which Padé approximation was used to study singularity formation in a fluid flow problem. Another study of this type is [17], which includes a test problem similar to (1.2).…”
Section: Introduction Many Nonlinear Pdes Have Solutions That Becomementioning
confidence: 99%